Pengaruh Kepemimpinan Transformasional, Iklim Inovasi, Efikasi Diri Terhadap Kreativitas Karyawan Pada Industri Pembuatan Gerabah Di Desa Kasongan, Kabupaten Bantul - Muhammad Yusuf Sholeh Sudjijana (Program Studi Manajemen Fakultas Ekonomi UST, 2019)
ABSTRACT The purpose of this study was to determine the Effect of Transformational Leadership, Innovation Climate, Self Efficacy on Employee Creativity in the Industry of Pottery Making in Kasongan Village, Bantul Regency on CV. Sokowatu Jaya, CV. Mata Hati, Jambul Ceramic in Kasongan, Bantul Regency, Yogyakarta. This research is a quantitative research. The population in this study are several employees